THE INFLUENCE OF ORGANIZATIONAL CLIMATE ON THE PRODUCTIVE RESULTS OF A SUPERMARKET COMPANY IN THE INTERIOR OF THE STATE OF SÃO PAULO - Martins Cardoso, Adriana; Dias Pereira, Lívia; Elaine Benetelli Geron, Regina (Revista Gênero e Interdisciplinaridade, 2025)
Organizational climate is a critical factor for performance and competitiveness in the retail sector, especially in supermarkets, which require high levels of customer interaction and operational efficiency. The main objective of this study was to analyze the influence of organizational climate on the productive results of a medium-sized supermarket company located in the countryside of the state of São Paulo. The methodology adopted was a case study with a mixed approach (qualitative and quantitative), of an exploratory and descriptive nature. Primary data were collected through a structured online questionnaire containing ten three-point Likert scale questions, applied to a convenience sample of 31 employees (approximately 26% of the total staff). Data analysis was carried out using descriptive statistics (percentage frequencies), allowing the identification of patterns and trends in employee perceptions. The results revealed a predominantly positive perception of the organizational climate in the company studied. More than 70% of participants agreed with the clarity and efficiency of interdepartmental communication and with the accessibility and receptiveness of leadership. Additionally, the absence of disagreement regarding mutual respect among colleagues suggests a healthy interpersonal environment. The analysis indicates that this positive climate directly contributes to employee engagement and satisfaction, being a determining factor for team productivity. The conclusion highlights that investing in a healthy work environment, characterized by participative leadership and recognition of employees’ efforts, is crucial for the success and sustainability of companies in the retail sector. The study provides practical insights for people management and continuous improvement, reinforcing the strategic importance of organizational climate as a competitive advantage.